PENGGUNAAN METODE AISMA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN BAGI ANAK BERKESULITAN BELAJAR MEMBACA - plb, author (program Studi Pendidikan Luar Biasa FKIP Universitas Sebelas Maret, 2013)
Purpose the research is to know the improvement the elementary reading capability of learning disability of reading in first year student SD Negeri I Bangak Boyolali after using AISMA Method in 2012/2013 academic year. This research using a classroom action research. Technique of collecting data is observation, test and document. Technique of analyzing data used comparative descriptive and critical analysis. The validity of the data is noun by triangulasi technique. The conclusion of this research is the use of AISMA method can improve capability in elementary reading for the first year student in this ability learning of reading of SD Negeri I Bangak Boyolali 2012/2013 academic years. Keyword: AISMA Method, Student with disability of reading,elementary reading